2022
DOI: 10.29132/ijpas.956825
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Sağlık Sektöründe 2013 -2019 Yılları Arasında İş Kazalarının İstatiksel Analizi

Abstract: Prevention of occupational accidents is one of the most important goals in occupational safety, but without understanding the causes of accidents, it is extremely difficult. The analysis of statistical data on occupational accidents has great importance in taking preventive measures. Therefore, the aim of this study is to analyze the statistical information of occupational accidents officially published between 2013-2019 in throughout Turkey and in the health sector. In the study, T.C. Social Security Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Yıldız and Özdemir (2021) tried to reveal the relationship between Turkey's development level and occupational accident statistics; For this purpose, they examined the relationship between the level of development indicators such as gross domestic product (GDP), average years of education and Human Development Index (HDI) data with fatal and non-fatal occupational accidents using simple regression analysis. Demir and Özay (2022) compared Turkey and various EU countries regarding general accident incidence rate and fatal occupational accident incidence rate based on the 2013-2019 occupational accident data obtained from SSI and EUROSTAT. They found that Turkey's fatal occupational accident incidence rate value for the examined period was much higher than the EU average.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yıldız and Özdemir (2021) tried to reveal the relationship between Turkey's development level and occupational accident statistics; For this purpose, they examined the relationship between the level of development indicators such as gross domestic product (GDP), average years of education and Human Development Index (HDI) data with fatal and non-fatal occupational accidents using simple regression analysis. Demir and Özay (2022) compared Turkey and various EU countries regarding general accident incidence rate and fatal occupational accident incidence rate based on the 2013-2019 occupational accident data obtained from SSI and EUROSTAT. They found that Turkey's fatal occupational accident incidence rate value for the examined period was much higher than the EU average.…”
Section: Literature Reviewmentioning
confidence: 99%